Asistensi Pelaporan SPT Wajib Pajak Pribadi Oleh Relawan Pajak Di Kota Dumai - Lailani Fitria; Billfan Syofyan; Alia Rahmah; Ika Desiana (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2023)
The service carried out by STIE Tuah Negeri tax volunteers at KPP Pratama Dumai in 2023 aims to assist taxpayers in reporting their tax obligations every year in the form of SPT reporting, besides that this service also aims to assist KPP Pratama Dumai in assisting personal taxpayers. The method used by tax volunteers in assisting taxpayers to report their annual SPT by using E-Filling. The conclusion from the community service activities carried out by STIE Tuah Negeri tax volunteers for approximately 1 month at the KPP Pratama Dumai was obtained data on the number of assisted taxpayers by team 3, a total of 622 tax residents consisting of 346 tax residents filling out the 1770 S PT type and filling out the SPT type 1770 SS numbered 277 tax citizens. It can be said that this amount increases the effectiveness and efficiency in assisting taxpayers to report their Annual SPT.